2021
DOI: 10.35848/1882-0786/ac3a3f
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the ferroelectric phase in Hf-based oxides by oxygen scavenging

Abstract: We propose an oxygen scavenging technique based on thermodynamic considerations of metal and oxygen systems to stabilize the ferroelectric phase and enhance the ferroelectricity in Hf-based oxides. By using an oxygen scavenging metal to control the oxygen vacancy concentration in Hf-based oxides, the effect of this oxygen scavenging technique in ferroelectric Hf-based oxides was systematically investigated. It was revealed that controlling the oxygen vacancies during the crystallization process is of vital imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Both experimental studies and first-principles calculations have reported that the content of oxygen vacancies affects the crystalline structures in HfO 2 -based thin films [59,60]. A large amount of oxygen vacancies facilitates the formation of the t-phase, while a low oxygen vacancy content is favorable for the m-phase [61].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both experimental studies and first-principles calculations have reported that the content of oxygen vacancies affects the crystalline structures in HfO 2 -based thin films [59,60]. A large amount of oxygen vacancies facilitates the formation of the t-phase, while a low oxygen vacancy content is favorable for the m-phase [61].…”
Section: Resultsmentioning
confidence: 99%
“…There exists a specific range of the oxygen vacancy content that is optimal for the stabilization of the metastable o-phase. Previous studies have revealed that the oxygen vacancies in HfO 2 -based thin films may result from the scavenging of oxygen by the electrodes [59][60][61]. In this study, the WO x interfacial layers (which can be clearly observed in the HRTEM images in figure 2) may be a result of oxygen scavenging in the HZO layer [40], which is also responsible for the pronounced ferroelectric performance of the Pt/HZO/W and W/HZO/W devices due to the formation of oxygen vacancies in the HZO layer.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroelectric HfO 2 films were commonly obtained by alloying with ZrO 2 to be a solid-solution Hf 0.5 Zr 0.5 O 2 (HZO), 9,10) or by doping with foreign elements, [11][12][13][14][15] or sometimes both. 16) The physical origin for the HZO films to be transformed into the ferroelectric phase is the presence of oxygen vacancies (V O ) 17,18) accompanied by the orbital-induced tensile stress in the films. 19,20) Therefore, HZO films with excess oxygen supply, in turn, result in the transformation to the monoclinic phase associated with high leakage current due to interstitial oxygens (I O ).…”
mentioning
confidence: 99%